The effect of initial diameter on rainbow positions and temperature distributions of burning single-component n-Alkane droplets. (July 2017) - Li, Haipeng; Rosebrock, Christopher D.; Wriedt, Thomas; Mädler, Lutz
Abstract: The effect of initial diameter on rainbow positions of burning single-component n-Alkane droplets has been investigated experimentally for the first time. The droplet diameters are determined with interferometric laser imaging for droplet sizing, and the temperature distributions inside burning droplets are assessed by rainbow refractometry together with a droplet combustion model developed in our previous work. Temperature gradients inside burning droplets influence rainbow positions, which first make the experimental scattering angles of the rainbow maxima increase and then decrease. The variations of initial diameter lead to variations of both experimental rainbow maxima and simulated temperature of n-Alkane burning droplets. Graphical abstract: The temperature gradient inside the burning droplet causes an increasing refractive index gradient from the surface to the core, which makes the rainbow rays bend towards the droplet core. As a result, the scattering angles of the rainbow maxima increase first. As the combustion proceeds, the core temperature of the droplet increases and temperature gradients inside droplet become weaker. The bent rainbow rays resume to be straight, resulting in a decrease of the scattering angles of the rainbow maxima. Highlights: The effect of initial diameter on rainbow positions of burning droplets is investigated experimentally for the first time. Temperature gradients inside burning droplets influence rainbow positions. The droplet initial diameters affect rainbow maxima and the simulated temperature.